Frontiers in Fontan failure: Innovation and improving outcomes: A conference summary. (20th October 2018) - Ephrem, Georges; Hebson, Camden; John, Anitha; Moore, Estella; Jokhadar, Maan; Ford, Ryan; Veldtman, Gruschen; Dori, Yoav; Gurvitz, Michelle; Kogon, Brian; Kovacs, Adrienne; Roswick, Meghan; et al.
Abstract: The initial "Frontiers in Fontan Failure" conference in 2015 in Atlanta, GA, provided an opportunity for experts in the field of pediatric cardiology and adult congenital heart disease to focus on the etiology, physiology, and potential interventions for patients with "Failing Fontan" physiology. Four types of "Fontan Failure" were described and then published by Dr Book et al. The acknowledgment that even Dr Fontan himself realized that the Fontan procedure "imposed a gradually declining functional capacity and premature late death after an initial period of often excellent palliation." The purpose of the second "Frontiers in Fontan Failure" was to further the discussion regarding new data and technologies as well as novel interventions. The 2017 "Frontiers in Fontan Failure: Innovation and Improving Outcomes" was sponsored by Children's Healthcare of Atlanta, Sibley Heart Center Cardiology, and Emory University School of Medicine. Future directions in the management of Fontan failure include further investigations into the risk of sudden cardiac death and how to properly prevent it, achievable interventions in modifying the Fontan physiology to treat or prevent late complications, and improved and refined algorithms in Fontan surveillance. Finally, further research into the interventional treatment of lymphatic‐related complications hold the promise of marked improvement in the quality of life of advanced Fontan failure patients and as such should be encouraged and contributed to.